Emergencia de las disidencias en Chile: una políticaficción para el estallido lesbofeminista y sus estelas performativas (1983-2010). - Gómez Tapia, Roxana (Nomadías, 2019)
In this article I offer a possible story of the lesbic feminist activism in Chile and its contributions to the emergence of dissidences. In particular, I support the thesis that feminist dissidences in Chile arises of the hand of lesbian activism. In order to argue this premise, I expose the confluences and divergences between these lesbofeminist activisms and, on the one hand, the movements led by "homosexuals" and the (hetero-)feminist movements. Finally, I suggest the contributions of the Chilean lesbofeminist movement to the emergence of other activisms that, despite their apparent distance or opposition, are part of the constellation that leaves its explotion.